The Extraction and Partial Characterization of Lunatin from Lima Bean (Phaseolus lunatus L.) - Ahmad Nafi'; Maria Belgis; Aisyah Fridannisa (Food, Agriculture and Natural Resources - NETWORKS, 2021)
Lima Bean (Phaseolus lunatus L.) contains a lectin called lunatin which is an antinutrient with antioxidant, antifungal, and antiproliferative properties. The purpose of this study was to determine the effect of different processing of Lima bean seeds, namely crushed dry seeds, Lima bean flour, and Modified Legume Flour (MOLEF). In addition, it delved into the differences resulting from different extraction temperatures (27ºC, 40ºC, and 50ºC) on the lunatin extract obtained. The results show that the total protein in dry seeds, flour and MOLEF Lima beans are 23.18%, 24.20% and 17.12%, respectively. The molecular weight of lunatin detected is 30.25 kDa; The highest antioxidant activity, marked at 83.58% , is obtained by lunatin extract from samples of crushed dried Lima beans, with an extraction temperature of 50ºC, while the lowest activity, 45.97%, is indicated by lunatin extract from MOLEF samples of Lima beans, with extraction temperature of 40ºC. Temperature variations in general do not affect the protein bands detectable. Likewise, the antioxidant activity also does not show antifungal activity against Aspergillus niger.